Analisis Rasio Likuiditas Dan Profitabilitas Sebagai Alat Ukur Kinerja Keuangan Pada PT Astra Argo Lestari Tbk Periode 2013-2022 - Fina Anggeraeni; Gatut Dradjad Purwoko (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to analyze financial performance based on liquidity ratios (current ratio and quick ratio) and profitability ratios at PT Astra Argo Lestari Tbk for the period 2013-2022. The method used is quantitative. The population used in this study were all financial statements of PT Astra Argo Lestari Tbk, where the sample in this study is the balance sheet and profit and loss statement for the period 2013-2022. The data analysis used in this study is financial ratio analysis, which includes liquidity ratios and profitability ratios. Specific analysis techniques include the calculation of current ratio, quick ratio, and net profit margin to assess financial performance. The results showed that the liquidity ratio (current ratio) was categorized as “not good” because the value was 175%, meaning below the average industry standard of Cashmere (2019) and (quick ratio) was categorized as “not good” because the value was 97%, meaning below the average industry standard of Cashmere (2019) this is because the company has not been able to pay off current liabilities using its current assets. Based on the profitability ratio (net profit margin) is categorized as “not good” because its value is 9%, which means it is below the average industry standard according to Cashmere (2019), this is due to the inefficiency of the company in maximizing its assets to generate profits.